Plasma cotinine levels and sleep disturbances in children exposed to environmental tobacco smoke - Özcan, Gizem; Zirek, Fazılcan; Çullas İlarslan, Nisa Eda and Günay, Fatih and Bakar Ateş, Filiz and Yılmaz, Özge and Çobanoğlu, Nazan (The Turkish Journal of Pediatrics, 2025)
Background. The relationship between sleep disturbances and exposure to environmental tobacco smoke (ETS) in children is a growing health concern. This study aimed to evaluate the association between ETS exposure and sleep disorders in healthy children, and to determine whether there is a difference in this relationship between secondhand smoke (SHS) and thirdhand smoke (THS) exposure. Methods. Healthy children aged 4–12 years who presented to the pediatric outpatient department were consecutively enrolled in this cross-sectional study. Plasma cotinine levels were measured to validate the exposure. The Children’s Sleep Habits Questionnaire was used to assess sleep disorders in all children. Results. Of the 203 children we evaluated, with a median (Q1-Q3) age of 8.3 (6–10) years, 99 (49.8%) were female. Children exposed to ETS had significantly more sleep disturbances than children who were not exposed to ETS (p = 0.042). However, there was no significant difference in the plasma cotinine levels (p = 0.239) or the prevalence of sleep disorders (p = 0.648) between children exposed to SHS and those exposed to THS. Conclusions. Exposure to both SHS and THS is associated with an increase in plasma cotinine and a higher prevalence of sleep disorders in children. These findings highlight the importance of reducing children’s exposure to all forms of ETS to promote healthy sleep and overall well-being.